Tax Socialization and MSME Assistance as an Effort to Encourage Tax-Aware Communities in Wonokerto Village - Yuliana Liska Savitri; Rochmad Bayu Utomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community service aims to provide an understanding of the Final Income Tax for MSMEs. The partners involved in this community service activity are two MSME players operating in Wonokerto Village, Turi District, Sleman Regency. The methods used include observation, counseling, training, and evaluation. This activity was carried out for one month with five meetings, namely on September 5, 17, 24, and October 3, 5, 2023. Activities were carried out in stages according to the method that had been designed by visiting partners one by one at their business locations. The result after the activity show an increase in the target partners' understanding of taxation, MSME Final Income Tax, how to calculate MSME Final Income Tax, and how to make a NPWP.